Relationship Between Linezolid Exposure and the Typical Clinical Laboratory Safety and Bacterial Clearance in Chinese Pediatric Patients - Huo, Ben-Nian; Wu, Yue-E.; Shu, Ling; Zhang, Ruo-Qi; Xiao, Jian-Wen; Li, Qian-Bo; Zhao, Wei; Jia, Yun-Tao; Song, Lin (Frontiers in Pharmacology, 2022)
Objectives: This study aimed to evaluate the association between LZD exposure and clinical safety and efficacy in Chinese paediatric patients. Methods: This retrospective cross-sectional study included patients ≤18 years old who received ≥3 days of LZD treatment between January 31, 2015, and December 31, 2020. Demographic characteristics, medication information, laboratory test information and bacterial culture results were collected from the Hospital Information System (HIS). Exposure was defined as AUC24 and calculated by nonlinear mixed-effects modeling program (NONMEM), version 7.2, based on two validated population pharmacokinetic models. Binary logistic regression analyses were performed to analyse the associations between AUC24 and laboratory adverse events, and receiver operating characteristic curves were used to calculate the cut-off values. Efficacy was evaluated by bacterial clearance. Results: A total of 413 paediatric patients were included, with an LZD median (interquartile range) dose, duration, clearance and AUC24 of 30.0 (28.1-31.6) mg/kg/day, 8 (4–15) days, 1.31 (1.29-1.32) L/h and 81.1 (60.6-108.7) mg/L∙h, respectively. Adverse events associated with TBil, AST, ALT, PLT, haemoglobin, WBC and neutrophil count increased during and after LZD treatment when compared with before medication (P<0.05), and the most common adverse events were thrombocytopaenia (71/399, 17.8%) and low haemoglobin (61/401, 15.2%) during LZD treatment. Patients with AUC24 higher than 120.69 mg/L∙h might be associated with low haemoglobin 1-7 days after the end of LZD treatment, and those with AUC24 higher than 92.88 mg/L∙h might be associated with thrombocytopaenia 8-15 days after the end of LZD treatment. A total of 136 patients underwent bacterial culture both before and after LZD treatment, and the infection was cleared in 92.6% (126/136) of patients, of whom 69.8% (88/126) had AUC24/MIC values greater than 80. Conclusions: Haematological indicators should be carefully monitored during LZD treatment, especially thrombocytopaenia and low haemoglobin, and a continuous period of monitoring after LZD withdrawal is also necessary. Since the AUC24 cut-off values for laboratory adverse events were relatively low, a trade-off is necessary between the level of drug exposure required for treatment and safety, and the exposure target (AUC24/MIC) in paediatric patients should be further studied, especially for patients with complications and concomitant medications.